Participatory journalism : guarding open gates at online newspapers - Singer, Jane B., 1955- (Chichester, West Sussex, U.K. ; Malden, MA : Wiley-Blackwell, 2011)
"Who makes the news in a digital age? Recent years have seen a dramatic change in the relationship between online media and the 'audience', and user-generated content is much more widely employed. The media space and control over what it contains are shared by bloggers, social networking pages, as well as traditional news outlets. Such an environment requires a dramatic conceptual and practical shift for journalists, who face a rapid and radical decline in their power to oversee the flow of information. The ability to productively incorporate user contributions within traditional media spaces is becoming a vital skill. This book is based on a collaborative research project by a team of journalism scholars from Europe, North America and Israel. It provides insights into how journalists at websites affiliated with leading national newspapers in ten Western democracies are thinking about, and dealing with, the inclusion of content produced and published by the people once viewed simply as 'the audience.' The journalist's control over media space, which was based to a large extent on their access to the means of disseminating information, has evaporated, and the space is now open to everyone. Participatory Journalism goes right to the heart of what journalists do, what journalism is, and what the role of news is in contemporary democratic society that has gone digital. "--Provided by publisher.
Machine generated contents note: Introduction: Sharing the Road -- The Impact of Participatory Journalism. Mechanisms of Participation: How Audience Options Shape the Conversation / Alfred Hermida -- The Journalist's Relationship with Users: New Dimensions to Conventional Roles / Ari Heinonen -- Managing Change. Inside the Newsroom: Journalists' Motivations and Organizational Structures / Steve Paulussen -- Managing Audience Participation: Practices, Workflows and Strategies / David Domingo -- User Comments: The Transformation of Participatory Space / Zvi Reich -- Issues and Implications. Taking Responsibility: Legal and Ethical Issues in Participatory Journalism / Jane B. Singer -- Participatory Journalism in the Marketplace: Economic Motivations behind the Practices / Marina Vujnovic -- Understanding a New Phenomenon: The Significance of Participatory Journalism / Thorsten Quandt -- Fluid Spaces, Fluid Journalism: The Role of the "Active Recipient" in Participatory Journalism / Alfred Hermida.
Includes bibliographical references and index.
Keywords: Electronic newspapers; Online journalism; Citizen journalism